The impact of labour Relations Act (Act 66 of 19995) at Vista University (Mamelodi Campus) from year 1981-2004 - Kuye, Jerry O. (University of Pretoria, 2013)
Dissertation (MAdmin (Public Administration))--University of Pretoria, 2007.